Penerapan Media Kahoot Pada Materi Stoikiometri untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas X - Nova Yokhebed Konengian; Fahyuddin; Muhammad Alim Marhadi (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
The purpose of this study was to find out the increase in student learning outcomes by applying kahoot media and knowing student responses to learning media. The research subjects were students of class X IPA 2 and IPA 3. The research design was pretest posttest control group design. The average pretest score for the experimental class was 45.29 and the posttest average score was 82.06. The pretest average score in the control class was 41.36 and the posttest average score was 66.06. The category of increasing cognitive learning outcomes of Normalized (N-Gain) students is classified as moderate both in the experimental class (0.65) and in the control class (0.43). The independent samples test results at the pretest showed a significance value (2-tailed) p = 0.057 > 0.05, the n-gain data showed a significance value (2-tailed) p = 0.000> 0.05, and the Mann-Whitney test results on the posttest data shows the significance value of Asymp (2-tailed) p = 0.000 < 0.05